Effects Of Cutter Geometrical Features On Machining Polyetheretherketones (PEEK) Engineering Plastic - Raja Abdullah, Raja Izamshah; Mohd Nawawi, Nurul Husna; Abu Bakar, Mohd Hadzley; Md Ali, Mohd Amran; Kasim, Mohd Shahir; Sulaiman, Mohd Amri (Universiti Malaysia Pahang, Malaysia, 2014)
-